Improving Reading Comprehension through the Implementation of Numbered Heads Together (NHT) - Sukma Nadi Ulandari, Ni Nyoman; Pramerta, I Gde Putu Agus; Sri Widiastuti , Ida Ayu Made (Journal on Studies in English Language Teaching (JOSELT), 2024)
It is impossible to separate comprehension from reading. The pre-test results indicated that the individuals struggled to recognize the text's general content, specialized information, textual meaning, and textual references. The goal of the current study was to determine whether Numbered Heads Together could help eighth grade students at SMPN 4 Kuta Utara with their reading comprehension. As a result, the researcher carried out an action research study in a classroom to meet the study's goal. The pre-test, post-test, and questionnaire were then given out by the researcher. From the pre-test, the students' mean scores significantly improved, going from 59.37 in cycle I to 71.87 in cycle II and 82.81 in cycle III. Moreover, the researcher used the questionnaire in the conclusion to get the extra supporting data. The result of the questionnaire showed the percentage of the 52.32% strongly agreed, 41.86% agreed, 5.37% undecided, 0.43% disagreed and 0% strongly agreed. Based on the results, of this study it could be concluded that reading comprehension of the eighth grade students of SMPN 4 Kuta Utara in academic year 2023/2024 can be improved through Numbered Heads Together.